Electroacupuncture inhibits mast cell degranulation via cannabinoid CB2 receptors in a rat model of allergic contact dermatitis. Issue 6 (December 2019) - Wang, Zhigang; Lu, Min; Ren, Jie; Wu, Xiaoxue; Long, Man; Chen, Longyun; Chen, Zebin
Objective: Cannabinoid CB2 receptors (CB2Rs) are mainly present on immune cells including mast cells, which participate in 2, 4-dinitrofluorobenzene (DNFB)-induced allergic contact dermatitis (ACD). In this study, we aimed to investigate whether inhibition of mast cell degranulation was involved in the anti-ACD effect of electroacupuncture (EA) at ST36 via CB2R. Methods: Sprague-Dawley rats were sensitised and challenged with DNFB following EA stimulation for 1 week. Ear swelling, serum IgE levels, local cytokine production and mast cell infiltration were evaluated. Additionally, rat peritoneal mast cells (RPMCs) were isolated and cultured for detection of CB2R expression, mitogen-activated protein kinase (MAPK) signalling activation and mast cell degranulation (including β-hexosaminidase and histamine release) in the presence or absence of CB2R antagonists. Results: EA treatment inhibited ear swelling, suppressed IgE and cytokine production, decreased the number of mast cells and curbed mast cell degranulation, which was associated with the inhibition of p38 phosphorylation in DNFB-induced ACD. Importantly, EA enhanced the expression of CB2R mRNA and protein in the RPMCs. CB2R antagonist AM630 but not CB1R antagonist AM251 effectively reversed the suppressive effect of EA on p38 activation, mast cell infiltration and degranulation. Conclusion: These findings provide more evidence to support the hypothesis that EA promotes CB2R expression in mast cells, which is followed by inhibition of the p38 MAPK pathway, potentially resulting in the anti-ACD effect of EA. This suggests that EA at ST36 may be an effective candidate therapy for treating inflammatory skin diseases such as ACD.